99mTc-DMSA renal scan and 99mTc-DTPA renography findings in patients with horseshoe kidneys: experience of a single institute (Bangladesh Journal of Nuclear Medicine, 2015)
Purpose: Horseshoe kidney is a congenital malformation that is found incidentally in many of the asymptomatic patients undergoing 99mTc- DTPA renography and 99mTc-dimercaptosuccinic acid (DMSA) renal scans in the nuclear nephrology division of National Institute of Nuclear Medicine & Allied Sciences (NINMAS). Scan findings of year 2012 and 2013 are demonstrated in this study. Methods: Few of the patients had known ultrasound reports of ectopic positioned or non-visualized kidney and mostly referred to our institute for 99mTc-DTPA renogram. Each diuretic renogram consisted of dynamic renal scan images obtained with camera in both anterior and posterior positions and15% window centered at 140 keV using 64 X 64matrix. Acquisition started with bolus injection of 99mTc-DTPA and dynamic images were acquired at 16-seconds/ frame for 75 frames. Intravenous injection of furosemide (1 mg / kg body weight) was given between 10-15 minutes of the study. They each underwent a 99mTc-DMSA renal cortical scan to confirm the horseshoe kidney. Results: In a 2-year period, 14 patients (5 children and 9 adults) with horseshoe kidney were found with age ranging from 6 to 43 yrs (mean + SD,23.93 ± 9.19) and a male to female ratio of 9:5.Nearly one third of patients (35.8%) were asymptomatic. Urinary tract infections or infection like symptoms were present in five (35.8 %), whereas few showed vague symptoms like flank pain (7.1 %), abdominal pain (7.1 %), gastrointestinal symptoms such as nausea (7.1 %), abdominal distension and fullness (7.1 %). Three kidneys (21.42 %) showed stasis of radioactive urine in the renal pelvic region prior to diuretic injection, suggesting functional obstruction. Only one kidney (7.17 %) showed frank unilateral hydronephrosis and 2(14.28%) showed obstructive nephropathy. There was no incidence of bilateral hydronephrosis. Gross parenchymal disease was seen in 2 (14.28%) and mild parenchymal insufficiency in 4 (28.57%). In 2 (14.28%) cases normal renal function with low GFR were observed. 35.71% patients show horseshoe kidneys with normal function and GFR with variation of sizes of two distinct kidneys. Of the 14 patients, asymmetrical renal cortical function between the two kidneys was found in10 (71.4%). Conclusion: 99mTc-DMSA renal scan and diuretic renogram with 99mTc-DTPA are the simple techniques for the assessment of the patency of horseshoe shaped kidneys, because they can evaluate functional anatomy and urodynamics. DOI: http://dx.doi.org/10.3329/bjnm.v17i1.22488 Bangladesh J. Nuclear Med. 17(1): 25-29, January 2014